KAJIAN MODEL REGRESI DATA PANEL PADA DATA INDEKS PEMBANGUNAN MANUSIA PROVINSI DKI JAKARTA TAHUN 2019-2023 - Widarti, Widiarti (MATHunesa: Jurnal Ilmiah Matematika, 2025)
Regression analysis on panel data is a regression technique that utilizes the panel data structure, which combines information from time series and cross section data. Panel data regression analysis in economics is usually used for Human Development Index (HDI) data. HDI is a measure used to assess the success of a region in developing the quality of life of its population. In panel data regression, there are three estimation models, namely CEM, FEM and REM. The CEM method assumes that the intercept and slope in the cross section and time series units are the same, the FEM method assumes that the intercept is different between cross section units, while the slope between cross section units remains the same, while the REM method assumes that differences in unit characteristics and time periods are accommodated in the residual model. As a result of this study, the best panel data regression model is using the Random Effect Model (REM) with individual effects. The variables of life expectancy, school expectancy, number of poor people and per capita expenditure are able to explain HDI in DKI Jakarta Province by 95.45%. Keywords: Panel Data Regression, HDI, Random Effect Model.